Relationship between dietary quality, tinnitus and hearing level: data from the national health and nutrition examination survey, 1999–2002. (3rd October 2017) - Spankovich, Christopher; Bishop, Charles; Johnson, Mary Frances; Elkins, Alex; Su, Dan; Lobarinas, Edward; Le Prell, Colleen G.
Abstract: Objective : To examine the relationship between the healthy eating index (HEI), a measure of dietary quality based on United States Department of Agriculture recommendations and report of tinnitus. Design : This cross-sectional analysis was based on HEI data and report of tinnitus. Study sample : Data for adults between 20 and 69 years of age were drawn from the National Health and Nutrition Examination Survey (NHANES), 1999–2002. The NHANES is a programme of studies, to assess the health and nutritional status of adults and children in the United States. Two thousand one hundred and seventy-six participants were included in the analytic sample. Results : Of the sample, 21.1% reported tinnitus within the past year and 11.7% reported persistent tinnitus, defined as tinnitus experienced at least monthly or greater. Controlling for age, sex, race/ethnicity, diabetes, noise exposure and smoking status, we found that with healthier diet (poorer vs. better HEI) there was decreased odds of reported persistent tinnitus [odds ratio (OR); 0.67; 95% confidence interval (CI) 0.45–0.98; p  = 0.03]. Conclusions : The current findings support a possible relationship between healthier diet quality and reported persistent tinnitus.